「其實你不懂我的心！」檢視臺灣吸引國際學生策略與學生來臺經驗落差之研究 "You Don't Know What Really Matters to Me!" Examining the Gaps Between Governmental Policies and Student Perspectives in International Student Recruitment Practices in Taiwan - 王秀槐 Hsiou-Huai Wang; 張珍瑋 Chen-Wei Cha (National Taiwan Normal University, 2016)
在競爭激烈的全球化時代，對於招募全球人才的理念與實踐進行省思更為重要。本研究以臺灣為個案，以瞭解一個非英語系國家如何採取招募策略以吸引國際學生。臺灣政府相關政策傾向於以全英語授課環境與足夠的獎學金吸引國際學生來臺，且期待進一步與國際學生的母國建立或堅固與臺灣之間的政治與外交關係。然而，對國際學生而言，他們來臺灣求學主要是受到學習中文／文化、良好社會環境與未來工作機會等誘因所吸引。本研究透過政策分析、問卷調查、學生訪談等方式瞭解在政府政策與學生期待之間產生的落差內涵，並提出藉由重新定位政策、建立國際學生輔導系統、強化臺灣利基等建議，以供未來招募國際學生政策與實踐的實質建議。 In the present era of competitive globalization, rethinking the ideals and rationales involved in recruiting global talent is crucial. This study used Taiwan as a case study to explore the approaches adopted by a non-English speaking country for recruiting international students. The Taiwan government believes that it should foster an English language teaching environment in universities and provide sufficient financial support to international students in order to establish and strengthen political and diplomatic relationships with the students' home countries. However, international students emphasize cultural, linguistic, social, and vocational elements in their motives for studying abroad. Gaps apparently exist between governmental policies and students' perceptions. Suggestions for bridging these gaps were provided with regard to policy clarification, system building, and niche strengthening in the age of global competition.